Sosialisasi Content Creator Pemula Bagi Remaja Karang Taruna Kelurahan Perwira Bekasi Utara Sebagai Pendorong Industri Kreatif - Devy Putri Kussanti; Dyah Mustika Wardhani; Rohani Lestari Napitupulu; Atun Yulianto (PT FORMOSA CENDEKIA GLOBAL, 2022)
Now with the increasingly advanced development of digitalization, many young people are starting to develop their wings by maximizing the use of the internet and social media. It's just that the majority of the use of new media is only limited to entertainment and information media. Even though there are many other advantages of social media that can be utilized optimally. This is what then encourages UBSI lecturers of Hospitality study program to hold community service activities for Youth Karang Taruna, Perwira Village, North Bekasi with a socialization model that carries the theme of novice content creators in the development of creative industries. In addition, there are also many community service participants who still lack information and understanding about content creators that are sustainable with the creative industry. The existence of community service this time with the socialization method is expected to provide additional references for today's millennial youth who mostly consume social media. Youth Karang Taruna is currently expected to be able to improve knowledge not only from formal education but from their participation with youth institutions/institutions in the surrounding environment so that they can maximize the culture of creativity and entrepreneurs in their youth.